Analysis of Errors in Writing Capital Letters in Description Essays in Semester II Students of the Sports and Health Education Study Program - Supriadin, Supriadin (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to find out errors in writing capital letters in writing Indonesian language papers, as well as to find out the factors that cause errors in writing capital letters in writing papers among second semester students of the Sports and Health Education Study Program, so that these errors can be reduced and corrected. The approach used in this research is a qualitative approach with descriptive research type. The research subjects consisted of 35 second semester students of the Sports and Health Education Study Program. The instruments used were interviews and documentation in the form of students' descriptive essays. The data analysis used in this research uses the Miles and Huberman model analysis, where in analyzing the data there are four activities, namely: data collection, data reduction, data presentation, and conclusions. The results of this research found errors in writing capital letters in descriptive essays in second semester students of the Sports and Health Education Study Program, including 465 errors in the high error category with a percentage of 70.77%. Meanwhile, writing errors in punctuation marks in descriptive essays for students in the second semester of the Sports and Health Education Study Program were in the low error category with 192 errors with a percentage of 29.22%. Factors that cause errors in writing capital letters in descriptive essays for students in the second semester of the Sports and Health Education Study Program, namely: Lack of student interest in essay writing activities, low student interest in reading, students' attitudes that are less concerned about writing capital letters, lack of student understanding of the rules. writing capital letters, less varied learning methods, less interesting learning media and current technological developments.